PENGARUH BUDAYA ORGANISASI PERUSAHAAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. PERUSAHAAN GAS NEGARA (PERSERO) Tbk MEDAN - Dedek Kurniawan Gultom (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
The objective of the research was to determine the effect of Organizational Culture and Performance on Motivation work in PT. Perusahaan Gas Negara (Persero) Tbk Medan. The population in this study were all permanent employees in the PT. Perusahaan Gas Negara in the Public Service, Finance, and Human Resources. Data were obtained by questionnaire from 100 respondents, using sampling techniques and in test valitidity and reliability. Data analysis techniques used classical assumption, Multiple Regression, T test, F test and determination.The results show that the Organizational Culture and Motivation significant or positive effect on Performance of partial employees and simultaneously significantly influence employee performance variables, and motivation variables have the most impact.